Genetic Diversity and Population Structure of Prunus persica Cultivars Revealed by Genotyping-by-Sequencing (GBS) - Ekaterina Vodiasova; Artem Pronozin; Irina Rozanova; Valentina Tsiupka; Gennady Vasiliev; Yuri Plugatar; Sergey Dolgov; Anatoly Smykov (Horticulturae, 2025)
Peach (Prunus persica (L.)) is one of the major commercial stone fruit crops. A genetic analysis of peach collections around the world is essential for effective breeding programmes, and the development of genomic and marker-assisted selection. This study focuses on research on peach collection at the Nikita Botanical Garden and aims to identify single-nucleotide polymorphisms (SNPs) at the genome level and analyse the genetic diversity, population structure, and the linkage disequilibrium (LD) pattern among 161 cultivars and hybrids. A total of 288,784 SNPs were identified using the genotyping-by-sequencing (GBS) approach and, after filtering, 7803 high-quality SNPs were used in the analyses. The 161 accessions were clustered into two groups using principal component analyses (PCoA) and seven populations by ADMIXTURE v.1.3 software, which was confirmed using phylogenetic analyses. The distribution of the genotypes within subpopulations reflected any fruit-related traits. A low level of genetic diversity and medium linkage disequilibrium was detected in peach cultivars. The observed heterozygosity was lower than expected and varied from 0.11 to 0.22 in genotypes with different origins. Our results based on 7803 SNPs were compared with those based on 12 microsatellite markers and differences in clustering, observed heterozygosity, and phylogeny were identified. This highlights the need to analyse collections using whole-genome approaches.